Experimental Investigation of Convective Heat Transfer of Nanofluids in a U-Type Heat Exchanger - Haghshenas, Masoud (Asian Journal of Chemistry, 2012)
Nanofluids are a class of heat transfer fluids created by dispersing solid nanoparticles in traditional heat transfer fluids. This study describes an experimental design and a numerical method to demonstrate the forced convective heat transfer using traditional fluid and zinc oxide/water (0.5 % v/v) nanofluid in a U-type double-pipe heat exchanger utilizing commercially available equipment. Experiments were conducted to determine the actual heat transfer rates and overall heat transfer coefficients under operational conditions using nanofluid and the heat transfer enhancement determined compared to fluids without nanoparticles. The experimental results show that the heat transfer rate and heat transfer coefficients of the nanofluid is higher than that of the base liquid (i.e., water). For a given hot fluid flow rate, the increase in the overall heat transfer coefficient is more forcible at high cold flow rate. The heat transfer rate and heat transfer coefficients increases with increase in mass flow rates of hot and cold streams.